Strongly Reciprocally p-Convex Functions and Some Inequalities - Hao Li; Muhammad Shoaib Saleem; Ijaz Hussain; Muhammad Imran (Journal of Mathematics)
In this paper, we generalize the concept of strong and reciprocal convexity. Some basic properties and results will be presented for the new class of strongly reciprocally p-convex functions. Furthermore, we will discuss the Hermite–Hadamard-type, Jensen-type, and Fejér-type inequalities for the strongly reciprocally p-convex functions.